Socio-demographic variables and crime reporting attitude in Nigeria - Odey, Stephen A.; Ojong, O. Odee; Agba, A. M. Ogaboh; Ojong, F. Eja; Emeka, Josephat O.; Ayuk, A. Achu; Akintola, Abayomi I.; Ogunsola, Olumayowa V. (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
The complexity involved in combating crime in different regions of the world makes information sharing fundamental in crime management. Unfortunately, crime victims, who should be in the frontline of providing this information to law enforcement agents are often lethargic and lackadaisical in doing so, owing to no fault of theirs. Thus, this paper explored the convergence between socio-demographic variables and crime reporting in Nigeria. Empirically, the study examined the relationship between the attitude of law enforcement agents, location of the crime, nature of the crime, and attitude to crime reporting. Mixed methods, including a cross-sectional survey and in-depth interview, was used to collect data from 1112 respondents through a multi-stage sampling technique. The quantitative data were analysed using simple linear regression; while, the qualitative data collected were analysed in themes as a complement to the quantitative data. Findings revealed that attitudes of law enforcement agents, crime location and nature of crime significantly affect attitude to crime reporting in the study area. The study concludes that there is a connection between selected socio-demographic variables such as attitudes of law enforcement agents, crime location, nature of crime and attitude to crime reporting. It was, therefore, recommended that law enforcement officers who fail to abide by the ethics of their profession and the standard procedure governing their interaction with both complainants and suspects should be severely sanctioned. Besides, law enforcement officers should be trained and re-trained in such areas as public relations and professional ethics guiding their operations